Varakhsha memory - Muhinova Rushana Jasurovna (Research Parks Publishing LLC, 2020)
Varakhsha is one of the most welcoming and enjoyable sites. Even the wind performing its lonely dance in the roofless empty halls of the palace sounds like a distant chorale. As to the Sogdian lunar god Mah, whose light floods the uninterrupted dreamy plains stretching from the foot of the citadel to the flat horizon, most people have not seen him so beautiful in any other part of the world.